Integrasi nilai-nilai multikulturalisme dalam pembelajaran untuk membangun toleransi - Musbar Harahap; Ramlan Saat; Reyhan Hidayat (Indonesian Counselor Association (IKI), 2024)
This research aims to explore the application of multicultural values in the learning process at SMA 4 Padangsidimpuan, with the main objective of fostering tolerance among students who come from diverse ethnic backgrounds. The main issue faced is ethnic differences that have the potential to trigger social conflict, thus hindering the creation of a harmonious learning environment. This research uses a qualitative approach with a case study design, with data collection techniques in the form of observation, in-depth interviews, and document analysis. Participants in this study included students, teachers, and principals. The results showed that the implementation of multicultural values through an inclusive curriculum, extracurricular activities, and planned social interactions can increase students' understanding of the importance of tolerance, appreciation of diversity, and living together in cultural differences. Overall, the integration of multicultural values at SMA 4 Padangsidimpuan has proven effective in building a culture of tolerance among students, although there are still challenges, such as limited understanding of multiculturalism among some students. The study recommends the need for additional training for educators and adjustments to the curriculum to place greater emphasis on teaching multiculturalism comprehensively. In addition, this study contributes to the development of future research, especially in examining more deeply how multicultural learning strategies can be implemented in schools with more diverse ethnic backgrounds and exploring the impact on social and academic relationships among students.